A Century of Science Publishing - A Collection of Essays - E.H. Fredriksson (ed.) (IOS Press, 2001)
Leading publishers and observers of the science publishing scene comment in essay form on key developments over the past century. The scale of the global research effort and its industrial organisation have resulted in substantial increases in the published volume, as well as new techniques for its handling. The former languages of science communication, like Latin and German, have given way to English. The domination of European science before WWII has been followed by large efforts in North America and the Far East. The roots of the National Library of Medicine lie in the US Army medical library, the US War effort gave rise to hypertext, and the US defense reaction to the Soviet Sputnik resulted in the Internet. The European invention of the Web has also changed the science publishing scene in the past five years. Some characteristic publishing enterprises, commercial and society owned, are described in a series of articles. These are followed by analysis of recent developments and possible changes to come. Functions of publishers, librarians and agents are brought into context. The future of publishing is currently being debated on open channels, while the historical dimension and professional input are sometimes lacking.